3(r+2)=-1(2r-4)

Simple and best practice solution for 3(r+2)=-1(2r-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(r+2)=-1(2r-4) equation:


Simplifying
3(r + 2) = -1(2r + -4)

Reorder the terms:
3(2 + r) = -1(2r + -4)
(2 * 3 + r * 3) = -1(2r + -4)
(6 + 3r) = -1(2r + -4)

Reorder the terms:
6 + 3r = -1(-4 + 2r)
6 + 3r = (-4 * -1 + 2r * -1)
6 + 3r = (4 + -2r)

Solving
6 + 3r = 4 + -2r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '2r' to each side of the equation.
6 + 3r + 2r = 4 + -2r + 2r

Combine like terms: 3r + 2r = 5r
6 + 5r = 4 + -2r + 2r

Combine like terms: -2r + 2r = 0
6 + 5r = 4 + 0
6 + 5r = 4

Add '-6' to each side of the equation.
6 + -6 + 5r = 4 + -6

Combine like terms: 6 + -6 = 0
0 + 5r = 4 + -6
5r = 4 + -6

Combine like terms: 4 + -6 = -2
5r = -2

Divide each side by '5'.
r = -0.4

Simplifying
r = -0.4

See similar equations:

| 3*(-4)= | | x^2-5=157 | | x^2+x^2=12 | | (-3)*4= | | 16-8x-12=24+20 | | (-2)*(-8)= | | 9-4x+7x+15= | | 9x+17-7x+17=2 | | -5=-15 | | 7x+10=9x-4 | | (3x^2+5x-1)+(x^2-2x-7)=0 | | 6x-x-2x+8=7x | | 2(6x+2x)=2(x*x+12) | | -9.79(27x-65)=78.24(6x+34) | | 3x(x-5)-3x*3*3=-30 | | 5(x-6)-x=0 | | 2x*x+3x=3 | | 2xx+3x=3 | | -(2x-7)=4 | | ln(30)+ln(x)=24ln(x+1) | | x+4=4x-10 | | 1.5p=-0.3 | | 2.2+p=1 | | 2y+3=5 | | z^2-8iz-16=0 | | 7c-3c=2c+24 | | 96-4y=84 | | 4+7n=n/6 | | 9q=99 | | y/7=.25 | | s-20=33 | | 23*x=46 |

Equations solver categories